2020
DOI: 10.1155/2020/2953128
|View full text |Cite
|
Sign up to set email alerts
|

Topping-Off Technology versus Posterior Lumbar Interbody Fusion in the Treatment of Lumbar Disc Herniation: A Meta-Analysis

Abstract: The treatment effects of topping-off technique were still controversial. This study compared all available data on postoperative clinical and radiographic outcomes of topping-off technique and posterior lumbar interbody fusion (PLIF). PubMed, EMBASE, and Cochrane were systematically reviewed. Variations included radiographical adjacent segment disease (RASD), clinical adjacent segment disease (CASD), global lumbar lordosis (GLL), visual analogue scale (VAS) of back (VAS-B) and leg (VAS-L), Oswestry disability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 51 publications
(108 reference statements)
1
5
0
Order By: Relevance
“…The scores of VAS, ODI, and JOA are commonly used indexes to assess the lumbar functions recovery and the postoperative efficacy. 35 Our results indicated that, in both groups, a significant decrease was observed in the VAS and ODI scores, and an increase was found in JOA scores at different post-surgical time points. No statistically significant difference was found for VAS leg pain, ODI, and JOA scores between the two groups at any follow-up time point.…”
Section: Discussionsupporting
confidence: 54%
“…The scores of VAS, ODI, and JOA are commonly used indexes to assess the lumbar functions recovery and the postoperative efficacy. 35 Our results indicated that, in both groups, a significant decrease was observed in the VAS and ODI scores, and an increase was found in JOA scores at different post-surgical time points. No statistically significant difference was found for VAS leg pain, ODI, and JOA scores between the two groups at any follow-up time point.…”
Section: Discussionsupporting
confidence: 54%
“…By collecting and consulting the published clinical literature, 8–10 the current authors found that topping-off instrumentation is often used following PLIF. Therefore, the PLIF procedure with conventional pedicle-based titanium rod fixation system (representing rigid fusion) at L4–L5 was initially simulated and used as a comparison baseline in this biomechanical study.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the biomechanical evidence for ASD after lumbar or lumbosacral fusion, [2][3][4] the topping-off technique, which combines rigid fusion with PDS devices such as PBDSS or ISP extended to adjacent levels, has been proposed to prevent hypermobility and overstress at the adjacent segment and thus decrease the incidence of ASD. 5,6,8 Several clinical studies have also demonstrated the effectiveness of topping-off instrumentation using PBDSS or ISP in ASD prevention. 9,10 However, biomechanical differences between the PBDSS-based and ISP-based topping-off instrumentations still remain unclear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous clinical trials and pairwise meta-analyses comparing various topping-off devices with spinal fusion surgery alone have been performed [ 13 , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] ]. However, because each study only includes one or two devices, integrating information on the relative efficacy of commonly used topping-off implants is difficult.…”
Section: Introductionmentioning
confidence: 99%